DEVELOPMENT OF ADENOVIRUS VECTORED VACCINE FOR AFRICAN SWINE FEVER VIRUS BASED ON NON-STRUCTURAL PROTEIN - Kameswari, Made Sumitha; Mahardika, I Gusti Ngurah Kade; Suardana, Ida Bagus Kade (Buletin Veteriner Udayana, 2023)
African swine fever (ASF) is a viral disease of swine which causes high mortality as well as causes high economic losses in domestic pig. This study describes the process to develop an adenovirus vectors ASF vaccine with A224L and A276R coding region and its immune response in mice. Synthetic DNA containing the A224L and A276R genes was amplified and cloned into the commercial plasmid pAdenoX with an infusion cloning kit. A total of 10 6 AdenoX-ASF-224L-276R viruses from transfected T293 cells were injected into six mice intra-muscularly, while the other six mice were given T293 cell extract and were treated as controls. Blood without anticoagulant was collected from the facial vein of mice at 1, 3, 5, and 7 weeks after injection. Antibodies against ASF were tested by ELISA using synthetic peptides of A224L and A276R as antigens. AdenoX-ASF_A276R_A224L recombinant was successfully generated and proven. Injection of recombinant AdenoX-ASF_A276R_A224L in mice can trigger an immune response at week 7 significantly higher (p=0.00) compared to control, while weeks 1, 3 and 5 are not different from control (p>0.05). Production of recombinant adenovirus in monolayer cells and virus quantification need to be improved. Booster testing needs to be done after the third week.